The role of music and multimedia in general education and teaching - Kurshumlia, Mimoza; Kokaj, Agon; Kurshumlia, Rajmonda (Edelweiss Applied Science and Technology, 2025)
This paper examines the use of music and multimedia as two key components for enriching the learning experience in general education. This multidimensional approach offers tremendous opportunities to increase student engagement and motivation by integrating powerful tools that support student-centered learning development. The integration of music and multimedia has a profound impact on stimulating critical thinking and improving memory. This study aims to shed light on how these two components can be used together to create dynamic and inclusive learning environments that enhance engagement and knowledge acquisition. The cognitive and emotional benefits of music and multimedia include stimulating creativity, improving communication and collaboration skills, and helping to create a learning environment that supports students' emotional well-being. Multimedia offers rich opportunities for illustrating concepts and creating learning situations that can be adapted to the diverse needs of students, while music creates an atmosphere that encourages deep and engaged learning. This study explores the ways in which music and multimedia can be integrated to provide a richer learning experience and prepare students for a technology-driven future. In addition to the theoretical component, a quantitative study was conducted. Data collected from surveys and the analysis of results will provide valuable suggestions for improving teaching practices.